(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Given the body of evidence for the complex links between gender norms and well-being, examining the effects of masculine norms on men’s health is increasingly becoming a focus of public health interest. This research is an attempt to shed light on the links between accepting different aspects of the hegemonic masculinity norms with self-esteem and life satisfaction on the one hand and depression, anxiety, stress, emotional closure and taking health risks on the other. The sample of participants included in the research consists of 310 men, ethnic Macedonians from 20 different cities in the country, aged between 20 and 30 years. The results of the correlational analysis between the eight included variables, in addition to clearly confirming the need for analysis of various aspects of masculinity on men’s behaviour, as opposed to using the general score only, suggest that for this age group, identification with hegemonic masculinity carries more potential risks than benefits. Thus, while the acceptance of the hegemonic ideal is positively related to self-esteem and life satisfaction in only a small number of aspects, most are associated with a reluctance to share emotions, depression, stress, anonymity, and health-threatening behaviours.